Accountant abilitiesand knowledge from the perspective of high school students (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: The abilities and knowledge of accounting professionals are crucial aspects for career consolidation, since the profession has gradually changed due to the adoption of international accounting standards and market dynamics. Thus, this study aimed at identifying the abilities and knowledge that high school students consider necessary for accountants' performance in the labor market. Method: The study is characterized as descriptive, with a quantitative approach to the problem. For data collection, high school students from the municipality of Três Lagoas, state of Mato Grosso do Sul, Brazil, were surveyed by the application of a structured questionnaire, to measure accountants' abilities and knowledge necessary for the exercise of the profession. Data were organized in Excel spreadsheets, using the Statistical Packages for the Social Sciences (SPSS) software for descriptive and factor analysis. Results: The set of variables presented in the research explained 60.91% of the abilities and knowledge that respondents judged necessary for the performance of accountants. Contributions: The gathering, identification and classification of the factors from the perspective of high school students allowed us to understand their perception of the accounting profession.
Keywords: accounting professional; ability; knowledge; factor analysis